Economic Impact of COVID-19 on High School Teachers; An Assessment of Teachers on Private High School from the Kathmandu Metropolitan, Nepal - Devkota, Nanu Maya (Interdisciplinary Journal of Management and Social Sciences, 2021)
The private sector education improving the overall education system has created a large employment opportunity for educated manpower of secondary-level education in Nepal. But unfortunately, there is almost no provision of economic, social, and employment-wise security and insurance for this human resources. Hence, this group of manpower gets heavily quivered by external natural and social factors like the COVID-19 pandemic.Being bound within Kathmandu metropolitan, this research has aimed to study the effect of COVID-19 on employment, income, and savings of the teachers involved in private high school (grade 11 and 12). This situation has arisen from the fact that many intuitions have been fully or partially shut down due to the global pandemic.  This study is quantitative research based on primary data. For this, the purposive sampling technique is used. This study computes the data through the questionnaire and the direct interview taken by 50 samples.Using paired t-test, a significant difference has been observed in the employment, income, and savings of the teachers, pre and during COVID backed and further evaluated by other descriptive statistics. The percentage change in meaningful employment, mean income and mean savings has been observed as 69.25%, 40.50%, and 86.95% respectively through the analysis of data.On evaluating the economic condition of teachers of private institutions, although it has been acceptable in sound environmental conditions, in extreme conditions like COVID-19, their economic condition is highly likely to get deteriorated. This deterioration is backed by the observation of this research and is highly significant.This research helps to forecast and manage the possible economic fluctuation of teachers, that may arise during a crisis like COVID-19. Furthermore, this research also implicates the government and concerned institutions to derive policies such as social security funds and other schemes for teachers to fortify their economic condition during abnormal situations.